Statins and Left Ventricular Function - Bakakos, Agamemnon; Oikonomou, Evangelos; Vogiatzi, Georgia; Siasos, Gerasimos; Tsalamandris, Sotiris; Antonopoulos, Alexios; Mourouzis, Costas; Fountoulakis, Petros; Vavuranakis, Manolis; Tousoulis, Dimitris (Current Pharmaceutical Design, 2017)
Background: Statins are a well-established class of drugs in both preventing coronary events and treating cardiovascular atherosclerotic disease, however their use in heart failure is still in debate. Objectives: To establish whether statins' pleiotropic actions in endothelium, inflammation, remodeling of the heart and anti-arrhythmic potential may be in favorable of heart failure patients. Methods: We proceed to literature search of English bibliography under the terms heart failure, statins, 3- hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors. Results: Various experimental and clinical trials on the use of statins in the different subtypes of heart failure according to the ejection fraction of the left ventricle have been conducted to conclude whether statins should be part of their patients' treatment. The evidence shows that the subgroup of patients with ischemic heart disease and those with preserved ejection fraction seems to have better results from the use of statins although randomized control trial in the total heart failure population did not show any benefit in mortality. Conclusion: Statins may be beneficial to left ventricle systolic and diastolic performance of heart failure patients however their result in mortality cannot be established based on current evidence.
Keywords: dyslipidemia